The biopsychosocial approach to addiction - Griffiths, Mark (Psyke & Logos, 2005)
For many people the concept of addiction involves taking of drugs. Therefore it is perhaps unsurprising that most official definitions concentrate on drug ingestion. Despite such definitions, there is now a growing movement that views a number of behaviours as potentially addictive including many behaviours which do not involve the ingestion of a drug such as gambling, sex, exercise, videogame playing and Internet use. This paper argues that all addictions consist of a number of distinct common components (salience, mood modification, tolerance, withdrawal, conflict and relapse) and that there are many other types of commonality on a psychological, biological, sociological, and cultural level. The paper argues that addictions are a part of a biopsychosocial process and evidence is growing that excessive behaviours of all types do seem to have many commonalities. This may reflect a common etiology of addictive behaviour and suggests that addiction may be a syndrome. It is argued that an eclectic approach to the studying of addictive behaviour appears to be the most pragmatic way forward in the field.